Development of the Healthy and Nutritious Traditional Game Dampu (Segi) to Increase Knowledge of Healthy Food in Early Childhood - Apriyansyah, Chandra; Nurita, Nurita; Priyanti, Nita; Patilima, Hamid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Healthy food knowledge among early childhood in Indonesia remains low, as children tend to reject vegetables and fruits while preferring snacks and sweetened drinks. This study aims to develop the traditional game Dampu Sehat Bergizi (SEGI) as an innovative learning medium to improve children’s understanding of healthy food. The research employed a Research and Development (R&D) approach using the ADDIE model, limited to the development stage, and was tested on 15 children aged 5–6 years at TK Larasati, South Jakarta. Data were collected through observation, teacher interviews, expert validation (nutrition, early childhood education, and media experts), and a pre-experimental one-group pretest–posttest design. Validation results indicated an average score of 90.2% categorized as “highly feasible.” Effectiveness testing showed a significant improvement, with the average knowledge score increasing from 86% (“adequate”) to 94% (“highly feasible”) after using the SEGI game. Children demonstrated high enthusiasm, active participation, and improved ability to identify healthy food categories. These findings confirm that the SEGI traditional game is effective in enhancing early childhood nutrition literacy through engaging, interactive, and culturally relevant learning experiences.